Insights into the interactions of enterococcus faecalis with protozoan predators - Chum, Chun Lok (2019)
Enterococcus faecalis is a commensal gut bacterium that is also frequently isolated from aquatic environments. Heterotrophic protists, commonly referred to as protozoa, are bacterivorous and are a major mortality factor for bacterial populations in aquatic environments. In order to survive, bacterial prey have evolved mechanisms for evasion of predators or for resistance to predation by these protozoa. In this study, E. faecalis, when co-cultured with Tetrahymena pyriformis, a ciliated protozoan, was found to resist digestion after being consumed by the ciliate. Live bacteria were found to be encased in expelled food vacuoles (EFVs) that provided protection against antibiotic treatment. EFVs were also released into the environment spontaneously regardless of nutrient availability. To determine the genetic and phenotypic effects of strong predation pressure on E. faecalis, it was co-cultured with the amoeba, Acanthamoeba castellanii, continuously over 30 days. Every 3 days, intracellular E. faecalis were collected from A. castellanii cells and inoculated into a fresh co-culture with the amoeba. Genomic DNA was extracted from the acclimated and non-acclimated isolates and sequenced to identify genetic changes that occurred during acclimation. As biofilm formation is one of the mechanisms which bacteria use to evade predation, it was hypothesised that exposure to A. castellanii would augment E. faecalis biofilm formation. Interestingly, the data showed that biofilm formation was reduced in acclimated strains as compared to non-acclimated strains. However, this reduced biofilm biomass phenotype was not sustained through subculturing, suggesting that this phenotype is not stable.